Phisycal model of boiling process on porous surface in limited space - Алексеїк, Ольга Сергіївна; Кравець, Володимир Юрійович (Eastern-European Journal of Enterprise Technologies, 2013)
Despite many publications concerning the features of the boiling process in a limited volume on smooth and extended surfaces, the majority of them deals with the forced liquid flow. At the same time, there is a need for studying the boiling process on porous surface in a limited space with natural current of heat carrier. The paper gives the results of experimental studies of the boiling process, which indicate the influence of the free space size on the heat dissipation intensity during the boiling on smooth and porous surfaces. Based on the experimental data analysis and the results of a series of visual studies, a physical model of the process has been suggested. In addition, the paper gives a number of systems of differential equations with boundary conditions, which can be used for constructing a mathematical model of the boiling process on the porous structure in a limited volume.